Faʻāliyātu Istikhdāmi Wasīlati Talking Stick Fi Istīʻābi al-Mufrādāt al-ʻArabiyyah Liṭulābi al-Faṣli al-Sābiʻ Bimadrasati Sudirman al-Mutawassiṭah al-Islāmiyyah Semarang - Noor Kalimah Octaviani; Dewi Rusliyani (KURAS Institute, 2023)
One of the problems at Sudirman Islamic Middle School is the lack of innovation in vocabulary teaching such that students’ vocabulary comprehension is low. To overcome this problem, the researcher uses the Talking Stick method to make learning enjoyable so that students are more active and enthusiastic about Arabic language topics. This research aims to determine the effectiveness of using Talking Sticks in vocabulary comprehension for seventh-grade students at Sudirman Islamic Middle School Semarang. This research is quantitative research, and the sample consisted of 40 students in the seventh-grade class C (control class) and class D (experimental class). In the method of collecting data, the researcher uses the pre-test, then the post-test, and the direct observation method. In analyzing the data, the researcher uses a parametric t-test of the “paired sample test” type to determine the effectiveness of the Talking Stick method in vocabulary comprehension for seventh-grade students at Sudirman Islamic Middle School, Semarang. The results of the research tool experiment were that the validity test of the tool was correct, the stability test of the instrument was stable, the different energy test was good, and the result of the difficulty level test the number of good questions was 14. The conclusion of the research tool experiment is that each of the research tool experiment questions is good. Based on research data at Sudirman Islamic Middle School Semarang shows that using the Talking Stick method is highly effective in vocabulary comprehension for seventh-grade students at Sudirman Islamic Middle School, Semarang. This can be seen from the t-test in the posthoc test conducted with the help of IBM Statistic SPSS 22 which showed a sign smaller than 0.05, or 0.02, which means that the hypothesis (H1) is accepted.